2012
DOI: 10.1080/01431161.2012.659356
|View full text |Cite
|
Sign up to set email alerts
|

Automated building extraction from IKONOS images in suburban areas

Abstract: The article addresses automatic building extraction from IKONOS images in suburban areas. In the proposed approach, we used a stereo pair of IKONOS images. Automatic photogrammetric methods of image matching were used to generate a digital surface model (DSM) and a digital elevation model. In further processing, single-image methods were used. The orthophotos of individual bands were created. The initial building mask was generated from the calculated normalized DSM (nDSM). The calculated normalized difference… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 28 publications
(25 reference statements)
0
15
1
Order By: Relevance
“…By reducing the dataset's size, we observed that the RMSE does not change. DSMs are incorporated in the process of image classification in urban/rural areas, for a holistic approach of land use/cover with improved results [21], or a targeted image classification, as is the case of urban green vegetation [3], but also in the process of the extraction of buildings [22,23], which resulted in more accurate results. The incorporation of DSMs in mapping elements in urban environments can benefit the current research by improving the results by incorporating texture and shape information apart from the spectral information [24,25].…”
Section: Resultsmentioning
confidence: 99%
“…By reducing the dataset's size, we observed that the RMSE does not change. DSMs are incorporated in the process of image classification in urban/rural areas, for a holistic approach of land use/cover with improved results [21], or a targeted image classification, as is the case of urban green vegetation [3], but also in the process of the extraction of buildings [22,23], which resulted in more accurate results. The incorporation of DSMs in mapping elements in urban environments can benefit the current research by improving the results by incorporating texture and shape information apart from the spectral information [24,25].…”
Section: Resultsmentioning
confidence: 99%
“…The building orientations are estimated using a simple new technique proposed in this article instead of building detection techniques already proposed in References [33][34][35][36][37]. Such previous techniques are not suitable to estimate the building orientations because they cannot automatically detect all buildings, which has been constantly argued in References [33,35,36]. Furthermore, the spatial resolution of post-disaster multi-looked PolSAR POAs is generally sufficient to cover multiple small buildings in one pixel; therefore, estimating dominant orientation of a group of buildings is appropriate for pre-disaster POA simulation.…”
Section: 2mentioning
confidence: 99%
“…Lines are representative features in the built-up areas; therefore, many urban applications have used them [35][36][37][38][39]. The Hough transform (HT) [40] is the common line extraction method in such applications.…”
Section: Line Extraction Using the Rghtmentioning
confidence: 99%
“…Buildings and structures are discerned in satellite or aerial images, either manually or automatically, by using an automatic building detection algorithm [29,30] followed by a RGA. Here, we note that [29] assumes that the building structures have convex rooftop sections.…”
Section: Discretization Of Spacementioning
confidence: 99%